"Double Trouble": Preoperative Embolization in a Case of Double Rupture of Hepatic Hemangioma during Pregnancy - Soumil Singhal; Mangerira Chinnappa Uthappa (Thieme Medical and Scientific Publishers Pvt. Ltd., 2019)
Hepatic hemangiomas are the most common benign space-occupying lesion of the liver. These lesions are associated with the gestational age of the patient. They can easily be missed and can rarely present with complications. Spontaneous rupture of hemangioma is a rare occurrence. Preoperative arterial embolization of hemangiomas plays a vital role to reduce intraoperative bleed during surgical resection. Here is a case of a young pregnancy presenting with a complicated outcome.